Recovery strategies for football players - Abaïdia, A.-E.; Dupont, G. (Swiss Sports & Exercise Medicine, 2018)
Recovery from intense efforts and matches demands special consideration, and recent years have seen the development of multiple new modalities which promise faster and better recovery. The world of professional football has taken notice, especially due to the repetition of matches and reduction of number of days in between for the best teams playing in the Champions League. Abd-Elbasset Abaïdia presented at the #SportSuisse2018 conference for Grégory Dupont, who was on duty with the World Cup winner French National team.With all the science, hype and innovation around recovery, you may be surprised to read about the effectiveness and the recommendations for each possible modality discussed in this paper. Everything that glitters is not gold, and the usual wise advice from your grandmother might have been true all along: eat, sleep, drink water. She might have been wrong on the "keep warm" advice, as cold exposure might have advantages.